Studies on the growth of Chlorella vulgaris in culture media with different carbon sources - Šoštarič, M. (Array, 2009)
Summary: Diminishing oil reserves, rising oil prices and a significant increase in atmospheric carbon dioxide levels have led to an increasing demand for alternative fuels. Microalgae have been suggested as a suitable means for fuel production because of their advantages related to higher growth rates, higher photosynthetic efficiency and higher biomass production, compared to other terrestrial energy crops. During photosynthesis, microalgae can fix carbon dioxide from different sources, including the atmosphere, industrial exhaust gases and soluble carbonate salts. To determine the most optimal conditions for the growth of Chlorella vulgaris in order to produce lipids that can be transformed into biodiesel fuel, different nutritional conditions were investigated. For this purpose, three media, namely Jaworski’s medium, an enriched solution from modified Dual Solvay process and natural mineral water, were prepared and analyzed for biomass production, chlorophyll content and lipid content. The best growth resulted in an enriched solution from the modified Solvay process. This medium was diluted in different dilution ratios (1:100, 1:50, 1:10) and the best results were obtained in a medium diluted in a 1:10 ratio on the fifth day of culturing (3.72 · 106 cells mL–1; 4.98 μg mL–1 chlorophyll a)